2018
DOI: 10.1002/ijc.31562
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of tumor‐associated macrophages in pancreatic neuroendocrine tumors

Abstract: Pancreatic neuroendocrine tumors (PNETs) represent a heterogeneous group of neuroendocrine neoplasms with varying biological behaviour and response to treatment. Although targeted therapies have been shown to improve the survival for patients at advanced stage, resistance to current therapies frequently occurs during the course of therapy. Previous reports indicate that the infiltration of tumor-associated macrophages (TAMs) in PNETs might correlate with tumor progression and metastasis formation. We aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 50 publications
(106 reference statements)
2
23
0
Order By: Relevance
“…Different immune cells (T cell, B cells, macrophages, dendritic cells, NK cells and mast cells) infiltrate the NETs making the TME immunosuppressed; this is more pronounced in P-NETs than SI-NETs probably due to a higher mutation rate in P-NETs[ 21 ]. CD+FoxP3+ T regulatory (Treg) and tumor-associated macrophage infiltration have been associated with high-grade NET[ 22 , 23 ] and poor prognosis. Soluble inhibitory factors secreted by NETs impair the maturation and function of dendritic cells, and as a result, antigen presentation to dendritic cells becomes impaired.…”
Section: Biology Of Netmentioning
confidence: 99%
“…Different immune cells (T cell, B cells, macrophages, dendritic cells, NK cells and mast cells) infiltrate the NETs making the TME immunosuppressed; this is more pronounced in P-NETs than SI-NETs probably due to a higher mutation rate in P-NETs[ 21 ]. CD+FoxP3+ T regulatory (Treg) and tumor-associated macrophage infiltration have been associated with high-grade NET[ 22 , 23 ] and poor prognosis. Soluble inhibitory factors secreted by NETs impair the maturation and function of dendritic cells, and as a result, antigen presentation to dendritic cells becomes impaired.…”
Section: Biology Of Netmentioning
confidence: 99%
“…In pancreatic cancer, many studies have confirmed that infiltrating macrophages mediate tumor progression in invasive tumors and early preinvasive pancreatic intraepithelial precursor lesions. Further studies have revealed that the depletion of TAMs by liposomal clodronate can dramatically reduce tumor metastasis [58,59].…”
Section: Impact Of Liposomal Nps On Macrophagesmentioning
confidence: 99%
“…The infiltration of tumor associated macrophages in pancreatic neuroendocrine tumors might correlate with tumor progression and metastasis formation. Krug et al investigated the effect of targeted tumor associated macrophage therapy in vitro and in vivo using liposomal clodronate [67]. By immunohistochemistry and tissue-micro-array, they assessed that clodronate arrests tumor progression and reduce tumor angiogenesis in the RIP1-Tag2 mice [67].…”
Section: Anti-angiogenic Inhibitors In Pre-clinical Studiesmentioning
confidence: 99%
“…Krug et al investigated the effect of targeted tumor associated macrophage therapy in vitro and in vivo using liposomal clodronate [67]. By immunohistochemistry and tissue-micro-array, they assessed that clodronate arrests tumor progression and reduce tumor angiogenesis in the RIP1-Tag2 mice [67]. However, combined therapy with liposomal Clodronate and the anti-angiogenic tyrosine kinase inhibitor sunitinib did not show any synergistic effects [67].…”
Section: Anti-angiogenic Inhibitors In Pre-clinical Studiesmentioning
confidence: 99%